Water-Dispersible CsPbBr3 Perovskite Nanocrystals with Ultra-Stability and its Application in Electrochemical CO2 Reduction - Chen, Keqiang; Qi, Kun; Zhou, Tong; Yang, Tingqiang; Zhang, Yupeng; Guo, Zhinan; Lim, Chang‑Keun; Zhang, Jiayong; Žutic, Igor; Zhang, Han; Prasad, Paras N. (Nano-Micro Letters, 2021)
Thanks to the excellent optoelectronic properties, lead halide perovskites (LHPs) have been widely employed in high-performance optoelectronic devices such as solar cells and light-emitting diodes. However, overcoming their poor stability against water has been one of the biggest challenges for most applications. Herein, we report a novel hot-injection method in a Pb-poor environment combined with a well-designed purification process to synthesize water-dispersible CsPbBr3 nanocrystals (NCs). The as-prepared NCs sustain their superior photoluminescence (91% quantum yield in water) for more than 200 days in an aqueous environment, which is attributed to a passivation effect induced by excess CsBr salts. Thanks to the ultra-stability of these LHP NCs, for the first time, we report a new application of LHP NCs, in which they are applied to electrocatalysis of CO2 reduction reaction. Noticeably, they show significant electrocatalytic activity (faradaic yield: 32% for CH4, 40% for CO) and operation stability (> 350 h). Highlights: 1 Water-dispersible CsPbBr3 nanocrystals (NCs) exhibit ultra-stability (>200 days) in water with only 20% decline of the initial photoluminescence intensity. 2 The as-prepared ultra-stable water-dispersible CsPbBr3 NCs showed high electrocatalysis activity (faradaic yield: 32% for CH4, 40% for CO) and operation stability (>350 h) for CO2 reduction reaction.